Application of Interactive Virtual Multimedia in Physics Learning - Lubis, Yenni Khairani (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2024)
Learning objectives can be achieved requiring strategies such as the application of appropriate learning media so that students are actively involved in the teaching and learning process. One of them is interactive multimedia. Multimedia is a combination of text, photos, graphics, audio, animation and video elements that are processed digitally. This research aims to determine the effect of using interactive multimedia in core physics learning on students' learning interest. The writing method in this research uses a qualitative approach with data collection methods in the form of literature studies. Using the literature study collection method, because the main source is entirely scientific work that is researched without any field observations from the researcher. The research results from this literature review show that interactive multimedia is feasible, interesting and effective as a physics learning medium, especially in core physics material in increasing students' interest in learning physics.